(untitled) (Faridpur Medical College Journal, 2016)
Significant number of Encephalitis patient was admitted in Faridpur Medical College Hospital (FMCH) in last years. There was an outbreak of Nipah Virus encephalitis in Faridpur in 2004. Among the 34 cases 26 patients were expired. After that, occurrence of disease is continuing. In this study a total number of 100 cases of clinically suspected encephalitis patients were studied for different clinical parameters and observed their clinical outcome. This is a retrospective study using data from hospital records. Among them 62% were male and 38% were female. Largest numbers of patients were under age group of 21-35 years, 46% of patients were from Faridpur district then 24% from Rajbari. Majority of patients were presented with neurological features (74%), 10% with pulmonary, 4% gastrointestinal, rest 12 % with combined neurological and pulmonary features. Maximum numbers (30%) of patients were attained treatment within 25 to 48 hours of onset of symptoms. Among them 78% of the patients recovered, 17% expired and 5% were referred. In this context, further prospective study is required to find out the epidemiological characteristics of Encephalitis in Faridpur region. Faridpur Med. Coll. J. Jan 2016;11(1): 20-22